A new species of chameleon (Sauria: Chamaeleonidae) from the highlands of northwest Kenya JAN STIPALA (UK), NICOLA LUTZMÁNN (Germany), PATRICK K. MALONZA (Kenya), LUCA BORGH-ESIO (USA), PAUL WILKINSON (UK), BRENDAN GODLEY (UK), MATTHEW R. EVANS (UK) - Stipala, Jan; Lutzmánn, Nicola; Malonza, Patrick K.; Borghesio, Luca; Wilkinson, Paul; Godley, Brendan; Evans, Matthew R. (Zootaxa, 2011)
A new species of chameleon, Trioceros nyirit sp. nov., is described from the northwest highlands of Kenya. It is morphologically similar to T. hoehnelii and T. narraioca, possessing a short rostral appendage, but differs from them by having a straight or weakly curved parietal crest and forward-pointing rostral projection. A phylogeny based on mitochondrial DNA shows that the proposed new taxon is a distinct clade within the bitaeniatus-group and a sister lineage to T. schubotzi. Its distribution appears to be restricted to the Cherangani Hills and adjacent Mtelo massif to the north. It is associated with afromontane forest edge, afroalpine ericaceous vegetation and also occurs in agricultural landscapes.